Recalling Deeds Immortal : Florida Monuments to the Civil War - Lees, William B. (Book collections on Project MUSE., 2014)
One hundred and fifty years ago, Florida was shaken by battle, blockade, economic deprivation, and the death of native sons both within and far outside its borders. Today, tributes to the valor and sacrifice of Florida's soldiers, sailors, and civilians can be found from the Panhandle to the Keys. Authors Lees and Gaske look at the diversity of Civil War monuments built in Florida between Reconstruction and the present day, elucidating their emblematic and social dimensions. Most monuments built in Florida honor the Confederacy, praising the valor of Southern soldiers and often extolling the.